Functional analysis of fibroblasts and macrophages in head and neck paragangliomas - Baruah, Paramita; Marshall, Jennifer L.; Nefla, Meriam; Pucino, Valentina; Adams, Holly; Turner, Jason D.; Gilbert, Sebastian; Powell, Emily; Neag, Georgiana; Monksfield, Peter; Irving, Richard M.; Croft, Adam P.; et al. (Frontiers in Endocrinology, 2024)
Background and aim Head and neck paragangliomas (HNPGN) are tumours that carry significant morbidity The role of the stroma in the pathogenesis of HNPGN is not completely understood. This study explores the profile of fibroblasts and macrophages in HNPGN. Methods Ten patients undergoing HNPGN surgery were recruited. CD68 and CD163 immunohistochemistry was performed for macrophage analysis; CD90 and podoplanin (PDPN) expression was examined to identify fibroblasts. RT-qPCR was performed on HNPGN tissue for macrophage- and fibroblast-associated molecules. Fibroblast cultures were established from HNPGN were analysed by RT-qPCR and flowcytometry. Confocal microscopy for MCT1 and MCT4 was performed in HNPGN. Results CD68 and CD163 expressing macrophages were noted in HNPGN. CD90 and PDPN expressing cells were present in HNPGN. RT-qPCR analysis showed expression of phenotypic and functional macrophage- and fibroblast-associated molecules in HNPGN. RT-qPCR analysis of fibroblasts cultured from HNPGN confirmed the expression of several molecules including PDPN at comparable levels to healthy tissue fibroblasts. Expression of FAP, MCT-1, insulin receptor (CD220) and insulin growth factor receptor-2 (CD222) was noted on HNPGN derived fibroblasts on flowcytometry. MCT1 and MCT4 were expressed in HNPGN tumour cells and stromal macrophages in-situ. Conclusion Fibroblasts and macrophages are present in the HNPGN tumour microenvironment, and several macrophage and fibroblast functional markers are expressed in HNPGN. Macrophages in HNPGN tissue express metabolic markers MCT1 and MCT4. Further analysis of the fibroblast and macrophage function in HNPGN will improve our understanding of their potential roles in tumour pathogenesis.